Remittances in the Pacific Region - Mineshima, Aiko.; Browne, Christopher (Washington, D.C. : International Monetary Fund, 2007)
Remittances are large and have grown substantially over the past decade in the Pacific region. This primarily reflects the impact of emigration due to low growth and limited employment prospects at home. Many Pacific emigrants settle abroad with their families for long periods, but maintain close links with their relatives, villages and churches. The paper finds that the altruistic motive for remittances remains much stronger in the Pacific region than in the rest of Asia, where investment considerations increasingly appear to predominate, especially for the large share of single citizens working abroad for limited periods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet